Guest editorial: Opportunities and challenges at the crossroads of communication and services - Lievens, Annouk; Neijens, Peter; De Pelsmacker, Patrick (International journal of service industry management, 2022)
First of all, society has changed such that communicating services for societal well-being issues has become increasingly important. [...]new actors have entered the service ecosystem, with new communication challenges and opportunities. [...]as a consequence of these developments, new types of services-customers interactions have emerged. [...]the papers focus on the co-creation of economic, social and environmental value in service ecosystems, wicked problems and the role of public relations, social activism in transformative service research, social media communication and crisis communication.